Regional Wage Differentials and the Spatial Convergence of Worker Characteristic Prices - Farber, Stephen C.; Newman, Robert J. (The Review of Economics and Statistics, 1989)
Stephen C. Farber, Robert J. Newman, Regional Wage Differentials and the Spatial Convergence of Worker Characteristic Prices, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 224-231